2013
DOI: 10.1038/ncomms2955
|View full text |Cite
|
Sign up to set email alerts
|

Hypothalamic proteoglycan syndecan-3 is a novel cocaine addiction resilience factor

Abstract: Proteoglycans like syndecan-3 have complex signaling roles in addition to their function as structural components of the extracellular matrix. Here, we show that syndecan-3 in the lateral hypothalamus has an unexpected new role in limiting compulsive cocaine intake. In particular, we observe that syndecan-3 null mice self-administer greater amounts of cocaine than wild-type mice. This effect can be rescued by re-expression of syndecan-3 in the lateral hypothalamus with an adeno-associated viral vector. Adeno-a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 29 publications
(33 citation statements)
references
References 35 publications
(45 reference statements)
1
30
0
1
Order By: Relevance
“…Indeed, virtually none of the regulators that were experimentally validated were significantly differentially expressed at the RNA level and yet they were confirmed as individual or synergistic phenotypic drivers following identification by regulatory network analysis, thus elucidating novel mechanisms of disease initiation/ progression [4,12,13,[41][42][43][44][45][46], chemosensitivity [15,28], and normal physiologic regulation [14]. Lately, we have successfully extended these methodologies to the study of neurological, neurodevelopmental, and stem cell phenotypes [35,42,47], and, more recently, to neurodegenerative phenotypes, resulting in a series of manuscripts, currently in review, where we report on the elucidation and experimental validation of novel genes mediating neurotoxicity in ALS [48], as well as biomarkers of AD progression [9].…”
Section: Creating the Assembly Manual Of The Alzheimer's Cellmentioning
confidence: 99%
“…Indeed, virtually none of the regulators that were experimentally validated were significantly differentially expressed at the RNA level and yet they were confirmed as individual or synergistic phenotypic drivers following identification by regulatory network analysis, thus elucidating novel mechanisms of disease initiation/ progression [4,12,13,[41][42][43][44][45][46], chemosensitivity [15,28], and normal physiologic regulation [14]. Lately, we have successfully extended these methodologies to the study of neurological, neurodevelopmental, and stem cell phenotypes [35,42,47], and, more recently, to neurodegenerative phenotypes, resulting in a series of manuscripts, currently in review, where we report on the elucidation and experimental validation of novel genes mediating neurotoxicity in ALS [48], as well as biomarkers of AD progression [9].…”
Section: Creating the Assembly Manual Of The Alzheimer's Cellmentioning
confidence: 99%
“…Subsequent analysis of syndecan-3 À/À mice showed that a lack of this protein resulted in higher rates of cocaine self-administration, an effect that could be reversed by viral-mediated rescue of syndecan-3 in the lateral hypothalamus. In line with this, overexpression of syndecan-3 in the lateral hypothalamus of wild-type mice also decreased cocaine self-administration (Chen et al, 2013).…”
Section: Box 1-cont'dmentioning
confidence: 86%
“…This is consistent with observations that plasticity-restricting PNN components are reduced after heroin self-administration (Van Den Oever et al, 2010) and protein expression of reelin is increased after cocaine self-administration (Host et al, 2010). Interestingly, an increasing number of studies show that experimental manipulations that reduce ECM breakdown or elevate ECM levels interfere with addictive behavior in different animal models of addiction, including behavioral sensitization (morphine, cocaine, and methamphetamine; Maiya et al, 2009;Mizoguchi et al, 2007;Nagai et al, 2004Nagai et al, , 2005b, CPP (morphine, cocaine, amphetamine, methamphetamine, and nicotine; Brown et al, 2007;Maiya et al, 2009;Mizoguchi et al, 2007;Nagai et al, 2004Nagai et al, , 2005bNagai et al, , 2006, cocaine self-administration (Chen et al, 2013), and reinstatement of heroine seeking (Van Den Oever et al, 2010). In contrast, enhancement of synaptic plasticity by ECM breakdown facilitates extinction of the drug memory (Xue et al, 2014), providing a substrate to suppress drug-seeking urges.…”
Section: Commonalities Of Addictive Drugs On Ecmmentioning
confidence: 96%
See 1 more Smart Citation
“…NARP is presynaptically secreted in a PNN dependent manner, recruiting AMPA receptors to cluster upon postsynaptic PV interneurons [85]. Expression of syndecan-3, a heparan sulfate proteoglycan component of the ECM that regulates ligand-receptor signaling, is induced by cocaine within the LH and significantly inhibits the motivation to self-administer cocaine [86]. Other candidate neuroplastic agents known to interact with PNNs include semphorin-3A, BDNF, and Otx2 [8789].…”
Section: Discussionmentioning
confidence: 99%